Energy, environmental, resource recovery, and economic dimensions of municipal solid waste management paths in Mexico city. (December 2021) - Juárez-Hernández, Sergio
Highlights: MSW paths assessed combine various waste technologies and separate collection schemes. Performance of the MSW paths was evaluated from a multi-dimensional perspective. Current MSW path has high GHG and low MSW recovery rates due to extensive landfilling. Considerable GHG mitigation and MSW valorization gains stem from better MSW practices. Switching to better MSW practices entails higher fossil energy use and economic costs. Abstract: Growing municipal solid waste (MSW) generation is a source of environmental, economic, and social concerns, especially in developing world megacities where poor MSW practices prevail. Mexico City (CDMX), one of the world's largest megacities, daily produces ∼ 13, 073 Mg of MSW whose management poses a tremendous challenge to local authorities and calls for additional research to conceive sound MSW strategies. This study evaluates the fossil energy use, GHG emissions, resource recovery, and economic cost dimensions of current and five alternative MSW paths in CDMX to compare their performance and identify more sustainable MSW practices for the megacity. Impacts and benefits from the MSW paths were modeled using 2018 MSW generation data, information supplied by local authorities, and literature values. Current MSW path consumes ∼ 387 MJfossil, generates ∼ 501 kg-CO2 e, and costs ∼ 57 USD2018 per Mg of MSW managed while it only valorizes < 33% of total MSW mostly via informal truck-picking. The alternative MSW paths considerably reduce GHG emissions (∼129–360 kg-CO2 e/Mg) and enhance MSW valorization (∼47–88%) though, they entail higher fossil energy consumption (447–582 MJfossil /Mg) and, in general, higher cost expenditures (43–208 USD2018 /Mg). Heavy reliance on landfilling, large GHG emissions, and low MSW valorization make current MSW path in CDMX unsustainable. Incineration-based MSW paths perform better in most aspects evaluated but their high costs seem prohibitive. Results suggest MSW paths featuring open windrow composting, mechanical–biological pre-treatment, material recovery facilities, and refuse-derived fuel production may be more appropriate to improve the sustainability of CDMX MSW management.